Efficiency of functioning of the staff development system at the enterprise - Мykola Dziamulych (Економічний форум)
The article examines the modern specifics of the formation of enterprise personnel development programs and defines the principles of ensuring the effectiveness of such programs in the conditions of intensification of technological development and the general complication of work. The requirements for employees with the wide implementation of digital and informational software products in the production process have been defined. The specifics of the organization of management of personnel development of the business entity in modern conditions have been studied. Attention is focused on the need of the enterprise to ensure a constant and continuous process of improving the qualifications and professional competences of employees. It has been proven that the practical formation of enterprise personnel development systems is definitely aimed at ensuring a general increase in the effectiveness of its professional activities, which implies an increase in labor productivity. Accordingly, it is determined that the final consequence of ensuring the functioning of personnel development systems in any case is an increase in the company's profit due to more effective use of the available aggregate human capital of the company. It was determined that the general orientation of personnel management systems in modern conditions should be aimed at ensuring a continuous process of professional development and professional training of the company's employees. It is this rhythmicity and continuity that is able to provide the business entity with prompt response to changes in the external environment. Thus, it is on this basis that the principles of efficiency in the management of personnel development, as a separate element of the personnel management system of the enterprise in general, should be formed. It has been proven that in modern economic conditions, the effectiveness of the personnel development system depends not only on its availability and compliance with the tasks of the strategic development of the enterprise, but also to a large extent on the effectiveness of the programs of professional development or retraining of the enterprise's employees. It was determined that the evaluation of the effectiveness of such programs involves the evaluation of changes in the level of labor productivity of personnel before and after the completion of programs to improve the level of their qualifications. Based on this, it was determined that the practical implementation of programs to improve professional competence can directly affect the efficiency of the enterprise's production activities